KEBIJAKAN PENDIDIKAN GRATIS BAGI MASYARAKAT KOTA BLITAR (Studi Implementasi Program Rintisan Wajib Belajar 12 Tahun Berdasarkan Peraturan Walikota Blitar Nomor: 8 Tahun 2015) - Wydha Mustika Maharani; Sukardi . (Universitas Merdeka Malang, 2016)
This research was done relation with the emergency of the problem about effort for poverty reduction understaken by governments who often considered lacking et maximal, because had a negative impact which make work lazy cultural and drape their life on the aid given by the government. The relation to that, so government of Blitar City has set a way to solve these problems by apply stub “Policy Free Education for The Civil Society at Blitar City through Program Rintisan Wajib Belajar 12 Tahun”. This research carrying to answer over (1) How is the implementation of program rintisan wajib belajar 12 tahun” at Blitar City, (2) How is the performance implementation, and (3) What is the dynamics that appear in the process of the implementation. This research used mixed methods approach with the use model of concurrent triangulation. The data collection techniques by interviews, observation, documentation and questionnaire. Based on the research results can be obtained that in the program implementation have been good enough, that was reviewed of some aspect: initiation taken by the mayor to development human resources through program rintisan wajib belajar 12 tahun”. Support a sufficient budget resources. The results of the implementation of seen from scoring output indicators are program of them: free education reached all students at public schools and private schools. Free education considered beneficial for less well of students and not influential for capable students. The support factor: implementing officials who prioritize education above other sectors. While factors that hampers: the weakness regulation “Program Wajib Belajar 12 Tahun” resulting tug diversion of authority to manage a high school education, the lack of role from parents in terms of children education, the lack of socialization from sides of school about free schooling program.DOI: https://doi.org/10.26905/pjiap.v1i2.441